2009
DOI: 10.1128/aem.01124-09
|View full text |Cite
|
Sign up to set email alerts
|

Dehalogenation Activities and Distribution of Reductive Dehalogenase Homologous Genes in Marine Subsurface Sediments

Abstract: Halogenated organic compounds serve as terminal electron acceptors for anaerobic respiration in a diverse range of microorganisms. Here, we report on the widespread distribution and diversity of reductive dehalogenase homologous (rdhA) genes in marine subsurface sediments. A total of 32 putative rdhA phylotypes were detected in sediments from the southeast Pacific off Peru, the eastern equatorial Pacific, the Juan de Fuca Ridge flank off Oregon, and the northwest Pacific off Japan, collected at a maximum depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 32 publications
8
99
0
Order By: Relevance
“…Further, genes for reductive dehalogenases were not detected with PCR using primers targeting these genes using MDA-derived DNA as template. Considering there is speculation that some marine subsurface DEH-affiliated bacteria could perform reductive dehalogenation (Adrian, 2009;Futagami et al, 2009;Valentine, 2010;Durbin and Teske, 2011;Wagner et al, 2012), the apparent absence of genes encoding reductive dehalogenases is worthy to note because this is the first genomic data from relatives of known organohalide-respiring DEH. Even if genes for reductive dehalogenases were in the missing genomic content, the DEH-J10 bacterium is considerably different to cultivated DEH because it does not appear to harbour a high proportion of genetic material dedicated to organohalide respiration.…”
Section: Electron Donating and Processing Reactionsmentioning
confidence: 99%
“…Further, genes for reductive dehalogenases were not detected with PCR using primers targeting these genes using MDA-derived DNA as template. Considering there is speculation that some marine subsurface DEH-affiliated bacteria could perform reductive dehalogenation (Adrian, 2009;Futagami et al, 2009;Valentine, 2010;Durbin and Teske, 2011;Wagner et al, 2012), the apparent absence of genes encoding reductive dehalogenases is worthy to note because this is the first genomic data from relatives of known organohalide-respiring DEH. Even if genes for reductive dehalogenases were in the missing genomic content, the DEH-J10 bacterium is considerably different to cultivated DEH because it does not appear to harbour a high proportion of genetic material dedicated to organohalide respiration.…”
Section: Electron Donating and Processing Reactionsmentioning
confidence: 99%
“…Several molecular tools have been developed for examining a broad range of rdhA genes in a given sample (site, isolate or mixed culture), including both microarray-based methods and PCR-based protocols [60][61][62][63]. Identification of novel reductive dehalogenase genes has primarily come from PCR studies [32,33,[35][36][37]39,40,42] and subsequently from genome and metagenome sequencing efforts [6,13,14,41,63], with each new organism or environment sampled increasing the known diversity of putative rdhA genes.…”
Section: Reductive Dehalogenasesmentioning
confidence: 99%
“…The first gene sequences encoding reductive dehalogenases were identified using classical reverse genetics approaches based on partial amino acid sequences of purified enzymes [30,31]. PCR and genome studies have since identified new sequences with high sequence identity to the characterized genes [6,13,14,[32][33][34][35][36][37][38][39][40][41][42]. Reductive dehalogenase genes (or reductive dehalogenase homologous genes (rdh) if the encoded protein has not yet been biochemically characterized) typically comprise an operon containing rdhA, the gene for the catalytically active enzyme (RDase if characterized, otherwise RdhA), rdhB, a gene encoding a putative membrane-anchoring protein [34], and sometimes one or more members of rdhTKZECD, genes associated with reductive dehalogenase genes [43].…”
Section: Reductive Dehalogenasesmentioning
confidence: 99%
“…Immediately after core recovery, 50 cm 3 of the innermost core sediment was taken using a 50 ml tipcut sterilized syringe. Study of the microbial population (Lipp et al, 2008;Morono et al, 2009;Futagami et al, 2009), the cultivation-based microbial communities (Kobayashi et al, 2008) and pore-water geochemical characteristics (Tomaru et al, 2009) are reported elsewhere. Strain JAM-BA0302 T grew at 15 u C on marine agar 2216 (MA; Difco) with the pH adjusted to pH 7.0 and was purified by more than five rounds of colony isolation at 15 u C using the same medium (Kobayashi et al, 2008).…”
mentioning
confidence: 99%